Effect of Pre-Emulsified Flaxseed Oil Containing Rutin on the Quality of Nemipterus virgatus Surimi Gel: Gelatinization Properties, Storage Stability, and Protein Digestibility - Qingguan Liu; Xiaobing Huang; Huanta Ma; Xinyi Qin; Pengzhi Hong; Xiaowen Pi; Chunxia Zhou (Foods)
Rinsing during surimi protein processing can result in the loss of essential nutrients, such as fats and minerals. Therefore, supplementing functional fats in a stable form can make up for the fat loss of surimi during the rinsing process. This research aimed to investigate the effects of incorporating pre-emulsified flaxseed oil with different concentrations of rutin (0, 0.5, 1.5, 2.5, and 3.5%, dissolved in flaxseed oil, w/v) to Nemipterus virgatus surimi on the gelatinization properties, lipid oxidation, and in vitro static simulated digestion characteristics of surimi gels. The results indicated that the addition of 1.5% rutin significantly improved the water-holding capacity and decreased the cooking loss rate of surimi gel (p < 0.05). The results of optical microscopy and scanning electron microscopy showed that the addition of 1.5% rutin promoted a denser network structure of surimi gel. Furthermore, the incorporation of rutin effectively slowed lipid oxidation in pre-emulsified flaxseed oil surimi gel. Compared with the gel group containing only pre-emulsified flaxseed oil, the addition of rutin significantly reduced the levels of volatile base nitrogen (TVB-N) and thiobarbituric acid reactive substances (TBARSs) in the gel and also mitigated the decline in acidity (p < 0.05). Moreover, the addition of rutin significantly inhibited the decrease in pH of surimi gel during storage (p < 0.05). In vitro static simulated digestion demonstrated that the addition of 1.5% rutin enhanced the protein digestibility from 71.2% to 77.2% of the surimi gel. Therefore, adding pre-emulsified oil containing an appropriate amount of rutin to surimi can not only compensate for the fat loss during the surimi rinsing process but also effectively improve the quality characteristics of surimi gels. This research will provide a theoretical basis for the effective addition of functional lipids in surimi products and the development of nutritious and healthy surimi products.